2017
DOI: 10.1007/s00204-017-1979-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicants, incidence of degenerative diseases, and therapies from the epigenetic point of view

Abstract: Epigenotoxicology is an emerging field of study that investigates the non-genotoxic epigenetic effects of environmental toxicants resulting in alteration of normal gene expression and disruption of cell function. Recent findings on the role of toxicant-induced epigenetic modifications in the development of degenerative diseases have opened up a promising research direction to explore epigenetic therapy approaches and related prognostic biomarkers. In this review, we presented comprehensive data on epigenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 193 publications
1
24
0
Order By: Relevance
“…These long-lasting health effects of early life stresses, can be attributed to specific epigenetic mechanisms such as altered DNA methylation patterns [ 37 ]. Previous studies have shown that exposure to environmental chemicals can induce epigenetic changes that persist for long periods of time and potentially affect physiology and health [ 41 ]. In the context of childhood lead exposure in humans and its potential adult health effects, it is of interest to know if lead exposures induce detectable epigenetic changes of any variety.…”
Section: Evidence That Lead Exposure Is Pro-diabeticmentioning
confidence: 99%
“…These long-lasting health effects of early life stresses, can be attributed to specific epigenetic mechanisms such as altered DNA methylation patterns [ 37 ]. Previous studies have shown that exposure to environmental chemicals can induce epigenetic changes that persist for long periods of time and potentially affect physiology and health [ 41 ]. In the context of childhood lead exposure in humans and its potential adult health effects, it is of interest to know if lead exposures induce detectable epigenetic changes of any variety.…”
Section: Evidence That Lead Exposure Is Pro-diabeticmentioning
confidence: 99%
“…Recently, an increasing number of scientific investigations have demonstrated that epigenetic alterations play an important role in the onset, establishment, and development of adverse health outcomes associated with environmental exposures (Marsit, 2015;Hodjat et al, 2017;Sun et al, 2018), including CVD (Alegría-Torres et al, 2013;Perez-Vazquez et al, 2017;Sun et al, 2018). Epigenetic changes include DNA methylation, non-coding RNAs (such as microRNAs), chromatin remodeling, and histone modifications (Tammen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stated another way, in the absence of any direct silicon-carbon bonding there is a natural and healthy utilization of silicon in the human body which is devoid of any pathologic biointegration of silicon into essential life-sustaining cellular molecules. Biochemical chaos caused by organosiloxanes also extends to the emerging discipline of epigenotoxicology, which studies adverse effects of environmental toxicants on gene expression and disruption of cell functions via changes in DNA methylation, alterations of histones, and changes to micro RNA (27) . Biophysics research is now capable of circuitously uniting: a) the odor and smell hypersensitivity observed in my breast implant recipients and fibromyalgia patients with b) the TILT observations of Dr. Claudia Miller.…”
Section: Biophysics Considerationsmentioning
confidence: 99%